Comparative Efficacy Of Pungai ( Pungamia Glabra) And Ivermectin Against Mange Infestation In Pigs - Ramesh, V.; Kumar, V. Ramesh Saravana; Sivakumar, K.; Singh, D.Anandha Prakash (Indian Journal of Veterinary Sciences and Biotechnology, 2012)
Ivermectin was found to be most effective followed by benzyl benzoate emulsion and pungan oil against sarcoptes species. It was found to be economical, effective and seven days observation period was sufficient. As ivermectin is easy to administer and less time consuming than topical application of emulsion/ oil of acaricides, the treatment with injectable ivermectin to eliminate mange has a distinct advantage in the control of mange infestation in pigs.